Design an embedded GPS auto time synchronizing system - Lai, K. J.; Pau, K. N. (2008)
An embedded Global Positioning System (GPS) auto time synchronizing system is designed and proposed. It is fully embedded microcontroller device that extract data string from GPS receiver module and parse it into a useful data for time synchronizing purpose in a unique dock using self-developed processing software.